CRM Concept to Increase Customer Loyalty an E-Commerce Case Study: JD.ID - Nicky Imanno, Christian Arry Budiman, Martinus Sugeng Rohadi, Emil R. Kaburuan, Gunawan Wang, Sfenrianto (International Journal of Advanced Science and Technology, 2020)
Sales of a product are not only done directly but can be through cyberspace intermediaries (e-commerce), but customers in e-commerce can not only interact actively but can also be passive. The passive interaction is due to lack of feedback from the system to customers with a lack of loyalty program. E-commerce JD.ID is an online shop that performs passive interactions. The online shop will be the object of research in this paper. The object of the research will be analyzed using the SWOT analysis method which is complemented by the concept of Customer Relationship Management (CRM) concepts in the form of People, Process, and technology. The SWOT analysis method is used to analyze the interrelationship of opportunities and threats to the external environment, as well as the interrelationship of opportunities and threats to the strengths and weaknesses of the company's internal, especially e-commerce. The expected outcome in this study is the CRM design (JD.ID) by applying the concept of CRM to increase Customer Loyalty.